MORPHOLOGICAL CHANGES IN OSTEOPOROTIC BONES: A COMPARATIVE ANALYSIS USING BIOCHEMICAL AND IMAGING METHODS - KHAN, QUA; KARIM, M; NAQVI, AZ; NOREEN, N; MAGSI, I; MANSOOR, E; MANSOOR, A; AKHTAR, N (Biological and Clinical Sciences Research Journal, 2024)
Osteoporosis leads to significant bone mass loss and structural deterioration, increasing fracture risk. Objective: This study explores the morphological changes in osteoporotic bones through a comparative analysis using biochemical markers and imaging techniques. Methods: A cohort of 55 osteoporotic patients underwent evaluation. Biochemical markers were measured, including serum calcium, phosphorus, alkaline phosphatase, and vitamin D. Imaging assessments involved dual-energy X-ray absorptiometry (DEXA) for bone mineral density (BMD) and high-resolution computed tomography (HRCT) for bone microarchitecture analysis. Correlations between biochemical data and imaging results were examined. Results: Biochemical analysis showed elevated alkaline phosphatase levels (mean: 210 IU/L) and widespread vitamin D deficiency (mean: 16 ng/mL). DEXA revealed significant reductions in BMD (mean T-score: -3.2), while HRCT detected substantial trabecular thinning (mean trabecular thickness: 0.12 mm) and increased cortical porosity. A strong inverse correlation (r = -0.75, p < 0.01) between BMD and alkaline phosphatase was observed, indicating a link between high bone turnover and reduced density. Vitamin D deficiency correlated with greater cortical porosity (r = 0.60, p < 0.05). Conclusion: The study highlights that integrating biochemical markers and imaging methods provides a comprehensive understanding of osteoporotic bone morphology. These findings emphasize the need for multi-modal diagnostic approaches to enhance osteoporosis management and fracture risk assessment.